Mortality Benefit of Recombinant Human Interleukin-1 Receptor Antagonist for Sepsis Varies by Initial Interleukin-1 Receptor Antagonist Plasma Concentration*. Issue 1 (January 2018) - Meyer, Nuala J.; Reilly, John P.; Anderson, Brian J.; Palakshappa, Jessica A.; Jones, Tiffanie K.; Dunn, Thomas G.; Shashaty, Michael G. S.; Feng, Rui; Christie, Jason D.; Opal, Steven M.
Abstract : Objective: Plasma interleukin-1 beta may influence sepsis mortality, yet recombinant human interleukin-1 receptor antagonist did not reduce mortality in randomized trials. We tested for heterogeneity in the treatment effect of recombinant human interleukin-1 receptor antagonist by baseline plasma interleukin-1 beta or interleukin-1 receptor antagonist concentration. Design: Retrospective subgroup analysis of randomized controlled trial. Setting: Multicenter North American and European clinical trial. Patients: Five hundred twenty-nine subjects with sepsis and hypotension or hypoperfusion, representing 59% of the original trial population. Interventions: Random assignment of placebo or recombinant human interleukin-1 receptor antagonist × 72 hours. Measurements and Main Results: We measured prerandomization plasma interleukin-1 beta and interleukin-1 receptor antagonist and tested for statistical interaction between recombinant human interleukin-1 receptor antagonist treatment and baseline plasma interleukin-1 receptor antagonist or interleukin-1 beta concentration on 28-day mortality. There was significant heterogeneity in the effect of recombinant human interleukin-1 receptor antagonist treatment by plasma interleukin-1 receptor antagonist concentration whether plasma interleukin-1 receptor antagonist was divided into deciles (interaction p = 0.046) or dichotomized (interaction p = 0.028). Interaction remained present across different predicted mortality levels. Among subjects with baseline plasma interleukin-1 receptor antagonist above 2, 071 pg/mL ( n = 283), recombinant human interleukin-1 receptor antagonist therapy reduced adjusted mortality from 45.4% to 34.3% (adjusted risk difference, –0.12; 95% CI, –0.23 to –0.01), p = 0.044. Mortality in subjects with plasma interleukin-1 receptor antagonist below 2, 071 pg/mL was not reduced by recombinant human interleukin-1 receptor antagonist (adjusted risk difference, +0.07; 95% CI, –0.04 to +0.17), p = 0.230. Interaction between plasma interleukin-1 beta concentration and recombinant human interleukin-1 receptor antagonist treatment was not statistically significant. Conclusions: We report a heterogeneous effect of recombinant human interleukin-1 receptor antagonist on 28-day sepsis mortality that is potentially predictable by plasma interleukin-1 receptor antagonist in one trial. A precision clinical trial of recombinant human interleukin-1 receptor antagonist targeted to septic patients with high plasma interleukin-1 receptor antagonist may be worthy of consideration. Abstract : Supplemental Digital Content is available in the text.